Respostas
respondido por:
0
resposta na imagem anexada
Anexos:
math314:
corrigida ;)
respondido por:
0
Oi Marcus
(2x - 1)² = (x + 5)²
4x² - 4x + 1 = x² + 10x + 25
3x² - 14x - 24 = 0
d² = 14² + 4*3*24 = 484
d = 22
x1 = (14 + 22)/6 = 36/6 = 6
x2 = (14 - 22)/6 = -8/6 = -4/3
(2x - 1)² = (x + 5)²
4x² - 4x + 1 = x² + 10x + 25
3x² - 14x - 24 = 0
d² = 14² + 4*3*24 = 484
d = 22
x1 = (14 + 22)/6 = 36/6 = 6
x2 = (14 - 22)/6 = -8/6 = -4/3
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás